PENTINGNYA JARINGAN INTERNET UNTUK PENDIDIKAN MATA PELAJARAN BTQ DI SD MUHAMMADIYAH TANJUNGKULON MASA PANDEMI COVID-19 - Rizki Wahid Hidayat (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The internet network is a tool that can make it easier to find something that is commonly used by some people, the internet network is also a medium used in the education process. Education is now a technology-based education in which all learning activities are carried out by including technology as a way to facilitate access to knowledge. In BTQ learning, which should be done face-to-face, during the covid-19 pandemic, learning is hindered by choosing online as the solution. During the ongoing COVID-19 pandemic, the education process was hindered, this time the online education process was carried out remotely.